RADIOLOGICAL FINDINGS OF MEDIASTINAL LYMPHADENOPATHY IN SARCOIDOSIS: IMPACT OF COUGH AND SMOKING HISTORY - Dimitrijevikj, Kristina (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Sarcoidosis is a systemic granulomatous disease with heterogeneous clinical manifestations, most commonly affecting the pulmonary system. The most typical manifestation include symmetric hilar and mediastinal lymphadenopathy. The aim of the study is is to evaluate the patterns of mediastinal lymphadenopathy in sarcoidosis detected on HRCT and correlate the nodes involvement in patients with cough and smoking history. Material and Methods: A total of 50 patients with confirmed sarcoidosis were evaluated at the University Clinic of Pulmonology and Allergology-Skopje. All patients underwent conventional chest radiography, followed by high-resolution computed tomography (HRCT). The HRCT scans were acquired using a 1 mm slice thickness and imaging was performed on a PHILIPS INCISIVE CT scanner. Results: According to the obtained results, lymphadenopathy did not present as a statistically significant difference in HRCT findings between smokers and non-smokers. In both groups, bilateral hilar lymphadenopathy was the predominant finding, observed in 66.67% of smokers and 70% of non-smokers. Calcified lymph nodes were detected exclusively in patients presenting with cough. A statistically significant difference was confirmed between the four disease stages regarding the prevalence of bilateral hilar lymphadenopathy (p = 0.003). Conclusion: Mediastinal lymphadenopathy, as identified through radiological imaging, is considered a hallmark in the detection of pulmonary sarcoidosis. HRCT remains the gold standard for identifying subtle pulmonary parenchymal abnormalities as well as for the accurate detection of mediastinal lymphadenopathy. Further clinical studies are necessary to clarify the potential association between cough, smoking history and lymphadenopathy in sarcoidosis. Key words: sarcoidosis, HRCT, lymphadenopathy, smoking, cough